Practices of Kindergarten Teachers in Achieving the nutritional knowledge of Kindergarten Children During the meal time - Al - Ghihab, Hasaa Abdel Latif (Journal of Educational and Psychological Sciences, 2019)
The study aimed to identify the practice of kindergarten teachers in providing، nutritional knowledge of the kindergarten child during the ، meal time. To achieve this، a descriptive method was used. The questionnaire was used as data collection tool. The sample consisted of (148) In the analysis of the data، the results of the study showed that the tool obtained an average of (2. 96 from 4. 00) and at the field level Axis (concept of nutritional knowledge (2. 89 of 4. 00)، followed by the difficulty of kindergarten teachers during the meal time، at an average (3. 49 of 4. 00)، both of which are rated (high)، while very high on (kindergarten teacher practices during the meal time at an average of (2. 50 of 4. 00) The teachers also showed that the meals attended by the children are healthy and that there is awareness among the families about the type of food provided to the children. .